ANALISIS SENGKETA MEREK DAGANG MENURUT UNDANG-UNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS ANTARA GS YUASA CORPORATION DENGAN PT GOLDEN SURYA JAYA (STUDI KASUS PUTUSAN PENGADILAN NOMOR 24/PDT.SUS-MEREK/2019/PN NIAGA.JKT.PST) - Popiani, Popiani; Chairunisa Irsad, Agri (Journal Evidence Of Law, 2022)
The study contains one of the example trademark disputes that occurred between GS Yuasa Corporation and PT Golden Surya Jaya which was contained in Court Decision Number 24/Pdt.Sus-Merek/2019/PN Niaga.Jkt.Pst., in the lawsuit the Plaintiff expressed an objection. on the GSJ brand on behalf of the Defendant used in the vehicle battery trade. In the thesis explain problems discussed are: how is the legal protection of registered trademarks in accordance with Law no. 20/2016 concerning Marks and how to assess the judge's consideration of Court Decision Number 24/Pdt.Sus-Merek/2019/PN Niaga.Jkt.Pst. fill with Law no. 20/2016 concerning Brands. The research method in this thesis is carried out through normative legal research which is carried out by collecting data through library data and as well as through juridical norms relating to aspects discussed at the Directorate General of Intellectual Property, and supported by Court Decision No. 24/Pdt.Sus-Merek/2019/PN Niaga.Jkt.Pst. The results of the study indicate that the regulation of trademarks is regulated in Law no. 20/2016. Legal protection is provided by the state only for the given mark. A person cannot be given legal protection when his mark is imitated by someone else, the mark has not been removed and the analysis of the decision and seen from the registration of the mark, namely the first to file registration carried out by the party who first registered the mark is considered the owner of the mark, then the decision is correct where the Judge ordered the Directorate General of Intellectual Property as a Co-Defendant to GSJ trademark registration No. IDM000597234 belongs to the Defendant. The judge is of the opinion that the GSJ mark with List No. IDM000597234 on behalf of the Defendant, in principle, has the same principle as the Plaintiff's GS mark which has been previously registered for similar goods.